Cultivating a Community of Change Through the Implementation of Shared Leadership Theory - Tiffany T. Boury (European Scientific Journal, ESJ, 2017)
In an effort to move toward a Shared Leadership Model, the researcher’s university administration directed all faculty and support staff to foster initiatives which promoted cross departmental research and collaboration. This study defines how pilot programs, in particular the New Faculty Induction program, were aligned with the framework of Shared Leadership and fostered the domains of Social Cohesion among participants.